1998
DOI: 10.1182/blood.v91.7.2601.2601_2601_2608
|View full text |Cite
|
Sign up to set email alerts
|

Hurler Syndrome: II. Outcome of HLA-Genotypically Identical Sibling and HLA-Haploidentical Related Donor Bone Marrow Transplantation in Fifty-Four Children

Abstract: Untreated patients with Hurler syndrome (MPSIH) experience progressive neurologic deterioration and early death. Allogeneic bone marrow transplantation (BMT) ameliorates or halts this course. The Storage Disease Collaborative Study Group was formed to evaluate the effectiveness and toxicity of BMT. Effectiveness was defined as engrafted survival with continuing cognitive development. Fifty-four patients deficient in leukocyte α-l-iduronidase enzyme activity (median age, 1.8 years; range, 0.4 to 7.9) received h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 27 publications
3
102
0
4
Order By: Relevance
“…This study also confirms the findings of others ( Finally, this study suggests that females undergoing HSCT for MPS IH may have increased mortality. The earliest reports of survival after HSCT for MPS IH included a large international study , showing a 5-year actuarial probability of survival of 64% for all patients (75% for those receiving a genetically identical sibling marrow, 53% for those receiving an HLA haplo-identical related marrow) (Peters et al 1996(Peters et al , 1998. The survival curves suggested that there were few, if any, deaths more than 2-3 years post-HSCT.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This study also confirms the findings of others ( Finally, this study suggests that females undergoing HSCT for MPS IH may have increased mortality. The earliest reports of survival after HSCT for MPS IH included a large international study , showing a 5-year actuarial probability of survival of 64% for all patients (75% for those receiving a genetically identical sibling marrow, 53% for those receiving an HLA haplo-identical related marrow) (Peters et al 1996(Peters et al , 1998. The survival curves suggested that there were few, if any, deaths more than 2-3 years post-HSCT.…”
Section: Discussionsupporting
confidence: 80%
“…Causes of death most frequently identified in the literature were transplant-related (within the first year), including viral infection, pulmonary hemorrhage (idiopathic pulmonary syndrome/diffuse alveolar hemorrhage), and graft-versus-host disease (GvHD) (Vellodi et al 1997;Souillet et al 2003;Boelens et al 2007Boelens et al , 2013Mitchelletal 2013). Most studies of 5-year survival probability report the predicted survival curve to have an extended plateau (no deaths) following the initial peri-transplant period (Peters et al 1998;Souillet et al 2003;Boelens et al 2013;Mitchell et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…63,64 Notably, HSCT has been shown to preserve cognition and increase survival in patients with Hurler syndrome if performed before the age of 2 years and before the onset of serious mental involvement. 51,[67][68][69] Clinical experience with HSCT is very limited for other MPSs. In MPS II, controversy still prevails surrounding the efficacy of HSCT in altering the course of the neurological decline despite observed somatic improvements.…”
Section: Current Non-pharmacological Therapiesmentioning
confidence: 99%
“…4 HSCT, introduced in 1981, restores endogenous production of the inherently deficient enzyme, and is most beneficial if performed prior to onset of cognitive decline (usually by 24 months of age) by arresting the neurodegenerative process. 5 The morbidity and mortality associated with HSCT alone are considerable and discouraging for parents (see Table 2). 6 Combined ERT-HSCT is being evaluated for benefit in ameliorating the high transplant-related morbidity and mortality in MPS I 7,8 (see Table 2 for comparison showing a significant decrease in overall mortality).…”
Section: Discussionmentioning
confidence: 99%